Moving a house with a team of horses through the mud down Front St., Nome, Alaska, August 27, 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Moving a house through Front St., Nome. Aug 27" Original image in Hegg Album 38, page 9.